MENUJU MODEL EKONOMI REGENERATIF: INTEGRASI KONSEP ISRĀF DALAM TRANSFORMASI SIRKULARITAS EKONOMI KONTEMPORER - Mohammad Romli (LPPM STAI Muhammadiyah Probolinggo, 2026)
The global ecological crisis stems from the ontological failure of the linear economic system, which separates material activity from spiritual values. This study aims to formulate an integrative framework between the Islamic prohibition of isrāf (excessiveness) and contemporary circular economy transformations to foster a regenerative model. Using a qualitative library research method, this research analyzes authoritative Islamic texts alongside regenerative economic discourses. The results confirm that while the circular economy provides technical mechanisms for resource retention, the concept of isrāf acts as a vital